In vitro enrichment of trace elements promotes rapid germination of Aspergillus conidia: a clinical concern for immunosuppressed and hyperglycemic patients - Nikhil A.; Tiwari A.K.; Tilak R.; Bhatia M.; Gupta M.K. (My University, 2025)
Background and Purpose: Trace elements play crucial roles in metabolic processes and serve as cofactors for various enzymes, although their specific involvement in fungal pathogenesis remains unclear. This study aimed to explore the impact of essential trace elements, iron (Fe), manganese (Mn), zinc (Zn), and copper (Cu), in conjunction with D-dextrose, on conidial germination and growth of Aspergillus fumigatus and A. flavus. Materials and Methods: The research involved determining the minimum inhibitory concentrations (MIC) of Fe, Mn, Zn, and Cu for Aspergillus ATCC strains. The study commenced by determining the MIC of the four trace elements, followed by evaluating the impact of selected trace elements on the kinetic growth and germination rates of Aspergillus species by the micro-broth method. Following MIC assessment, optimized concentrations of the trace elements (~140 and 550 pM) and various concentrations of D-dextrose (1-3% w/v) were introduced to assess their effects on fungal growth in RPMI 1640 broth. Growth was measured in optical density, while conidial germination rates were also observed. Results: The MICs for Fe, Mn, and Zn exceeded 35 µM, while Cu exhibited lower MICs of 2 and 7.6 µM against A. fumigatus and A. flavus, respectively. Fe, Mn, Zn, and Cu significantly enhanced fungal growth in both Aspergillus species at optimized concentrations. Additionally, growth rates increased proportionally with higher D-dextrose concentrations. Notably, combining enriched trace elements and D-dextrose resulted in up to 98% conidial germination. Conclusion: The findings demonstrate that optimized concentrations of essential trace elements and D-dextrose significantly promote conidial germination and growth of Aspergillus species in vitro. These results suggest that trace element supplementation might have important implications for immunocompromised and hyperglycemic patients. Further studies are warranted to explore the interactions between these micronutrients in fungal physiology and pathogenesis. Copyright© 2024, Published by Mazandaran University of Medical Sciences on behalf of Iranian Society of Medical Mycology and Invasive Fungi Research Center.